2009
DOI: 10.1089/jmf.2008.0136
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Evaluation of the Essential Oil fromMentha longifoliaL. subsp.capensisLeaves in Rats

Abstract: The effects of the essential oil from the leaves of Mentha longifolia L. subsp. capensis on some biochemical parameters of Wistar rats were studied. The oil at 125, 250, 375, and 500 microL/kg of body weight reduced (P < .05) the red blood cells and lymphocytes with no definite pattern on the white blood cells and mean cell volume. The doses significantly increased the neutrophils, monocytes, large unstained cells, liver-body weight ratio, and serum concentrations of cholesterol, triglyceride, high-density lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…However, although the pattern of the traditional use of ML is safe regarding the amount of pulegone as mentioned before, the essential oil from ML may increase the liver activity in rats at the lowest dose given. Thus, it should be moderately and carefully used because it may not be completely "safe" (Odeyemi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, although the pattern of the traditional use of ML is safe regarding the amount of pulegone as mentioned before, the essential oil from ML may increase the liver activity in rats at the lowest dose given. Thus, it should be moderately and carefully used because it may not be completely "safe" (Odeyemi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The RBC indices, MCV, MCH and MCHC showed marginal decrease in the extract treated compared to the control. The importance of calculated blood indices in anemia diagnosis has been reported [23] . The non-significant difference on the RBC indices suggested that the extract did not affect a change in the average size of RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…It can also be used to determine the extent of deleterious effect of foreign compounds, including plant extracts, on the blood of the albino rats [2]. Heamatological parameters can also be used to explain blood relating functions of plant extract or its products [2,23,24].…”
Section: Effect Of Cooked (50 Minutes) C Plagiosperma Seed On the Hamentioning
confidence: 99%
“…Eosinophiles are responsible for allergic reactions and disorders, It increases with allergic conditions and decreases with stress and/or infection [1,2,15]. Neutrophiles is mainly responsible for phagocytosis of pathogenic micro organism during the first few hours after their entry into tissues [1].…”
Section: Canavalia Plagiosperma Pipermentioning
confidence: 99%
See 1 more Smart Citation